The impact of armed conflict on economic performance: Evidence from Rwanda - Pieter Serneels; Marijke Verpoorten (Institute for the Study of Labor (IZA), 2012)
Important gaps remain in the understanding of the economic consequences of civil war. Focusing on the conflict in Rwanda in the early 90s, and using micro data to carry out econometric analysis, this paper finds that households and localities that experienced more intense conflict are lagging behind in terms of consumption six years after the conflict, a finding that is robust to taking into account the endogeneity of violence. Significantly different returns to land and labour are observed between zones that experienced low and high intensity conflict which is consistent with on-going recovery. Distinguishing between civil war and genocide, the findings also provide evidence that these returns, and by implication the process of recovery, depend on the form of violence.
Keywords: O0; E2; O5; 330; civil war; economic growth; Rwanda; human capital; Bürgerkrieg; Kriegsfolgen; Wirtschaftswachstum; Humankapital; Ruanda